Demonstration Experiments in the Lecture Room Environment : Final Report for a 1998 Teaching Development Grant (Individual). - Riley, Mark J. (University of Queensland, 2000)
This is a final report for a 1998 National Teaching Development Grant (Individual) funded by the Committee for University Teaching and Staff Development. The report summarises the project and provides justification and an educational rationale for its development. Demonstration experiments are described and evaluated.